Similar predator aversion for natural prey with diverse toxicity levels. (July 2019) - Chouteau, Mathieu; Dezeure, Jules; Sherratt, Thomas N.; Llaurens, Violaine; Joron, Mathieu
Abstract : Müllerian mimicry between chemically defended species arises from selection exerted by predators in which individuals benefit from higher survival when they share the same warning signal. However, despite sharing warning signals, co-mimetic species harbour a diversity of toxins at a range of different concentrations. This variation may affect the rate of predator avoidance learning and therefore the dynamics of mimicry. Here, to understand the nature of mimetic relationships in natural communities of butterflies and moths, we compared protection against predators induced by chemical defences of 13 lepidopteran species belonging to six mimicry complexes. Protection was estimated by quantifying the extent of avoidance learning, using domestic chicks, Gallus gallus domesticus, as model predators. We showed that most co-mimics were avoided at similarly high rates, with the exception of two species eliciting markedly slower rates of avoidance. Assuming our model and natural predators behave similarly and cannot distinguish co-mimics visually, the similar avoidance learning they induce supports the contention that mutualistic relationships among these co-mimetic species might be predominant in natural communities, despite large variation in toxin concentrations. Indeed, by comparing our estimated avoidance learning rate to mean toxin concentration, we found that prey with a two- to three-fold difference in toxin content generated similar avoidance learning indices. This lack of a direct relationship between prey defence level and predator avoidance learning points to alternative evolutionary mechanisms promoting the evolution of high levels of toxins.